2009
DOI: 10.1086/599841
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Variant Surface Antigens ofPlasmodium falciparum–Infected Erythrocytes Are Associated with Protection from Treatment Failure and the Development of Anemia in Pregnancy

Abstract: Background In pregnancy associated malaria (PAM), Plasmodium falciparum infected erythrocytes (IEs) express variant surface antigens (VSA-PAM) that evade existing immunity and mediate placental sequestration. Antibodies to VSA-PAM develop with gravidity and block placental adhesion or opsonise IEs for phagocytic clearance, protecting women from anemia and low birth weight Methods and findings Using sera from 141 parasitemic pregnant Malawian women enrolled in a randomized trial of antimalarials and VSA-PAM-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 39 publications
2
59
0
1
Order By: Relevance
“…Our choice of a pool of three P. falciparum isolates (MOZ2, R29 and E8B) was believed to give reasonable representation of the variants expressed in the population. Other studies in different age groups have found variable results; some reported associations between VSA antibodies and protection but others have not (Marsh et al 1989;Bull et al 1998;Giha et al 2000;Dodoo et al 2001;Feng et al 2009), therefore the role of VSA antibody responses in protection in infancy and early childhood needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Our choice of a pool of three P. falciparum isolates (MOZ2, R29 and E8B) was believed to give reasonable representation of the variants expressed in the population. Other studies in different age groups have found variable results; some reported associations between VSA antibodies and protection but others have not (Marsh et al 1989;Bull et al 1998;Giha et al 2000;Dodoo et al 2001;Feng et al 2009), therefore the role of VSA antibody responses in protection in infancy and early childhood needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This immunity is acquired as a result of antigenic stimulation through repeated parasite infections from early childhood onwards [109] but exposition to infection during fetal stages lead to impairment of memory responses and increased rates of infection later in life [110]. Susceptibility to malaria during pregnancy has been attributed to lack of antibodies able to block the binding of P. falciparum to CSA in the placenta [111] and to facilitate opsonic uptake by phagocytes [112][113][114]. The CSA adhesion phenotype is specific to placental parasites and it has been linked to the expression of a unique var gene (var2csa) [80,82].…”
Section: Specific Antibody Responsesmentioning
confidence: 99%
“…[7][8][9][10] Fortunately, antibodies (Abs) to placental-binding IE reduce sequestration and improve pregnancy outcomes. [11][12][13][14][15][16][17] Abs to VAR2CSA are acquired over successive pregnancies that reduce the risk of placental malaria (PM). 7,12,15 Intermittent preventive treatment (IPT) with sulfadoxinepyrimethamine (SP) and insecticide-treated bed nets (ITN) are the recommended standard of care for preventing malaria during pregnancy in areas with moderate to high transmission.…”
Section: Introductionmentioning
confidence: 99%